Probleme și soluții posibile pentru reforma sistemului de protecție socială și de servicii sociale - Mărginean, Ioan (Calitatea Vieții, 1994)
This article presents a personal point of view for solving some of the problems confronting social protection and social services systems in Romania. The author argues for a general reform and defines a moderate welfare state for transition period. He insists on the necessity of preliminary reduction of social protection burden through property, creating the social budget with contributions from population, enterprises and state, extension of social protection covering, introduction of new benefits and social services, creating an internal economy in social field.